TINDAK PIDANA KEKERASAN SEKSUAL STUDI KOMPARASI PSIKOLOGI HUKUM DAN PSIKOLOGI ISLAM - Muthahir, Ardi; Fuadi, Ahmad; Rizki Amaliah (Faculty of Law Universitas Lancang Kuning, 2024)
In reality (das sein) there are still many people who try to break the law. One of the crimes is sexual violence. Cases of sexual violence against children continue to increase from time to time. Sexual abuse is a gender issue that involves various aspects of human life such as morality, religion, beliefs, gender, and other factors. The crime of sexual violence causes a person to be pessimistic in looking at life. Islam prohibits sexual violence because it has a bad impact. Perpetrators of sexual violence are also considered to have violated serious religious boundaries. The Islamic psychological approach provides a way to not only punish, but also seek recovery and repair from a religious perspective.